(untitled) (Tibuana : Journal of Applied Industrial Engineering, 2026)
Determining delivery routes that minimize total cost is a key issue in goods distribution. This study focuses on a bottled drinking water (AMDK) company in City X that distributes its products to multiple retail outlets with different service time requirements. Such conditions fall within the scope of the Vehicle Routing Problem with Time Windows (VRPTW). In this study, a soft time windows approach is adopted, allowing vehicles to serve retailers beyond their specified time limits at the expense of penalty costs. The main objective is to identify optimal delivery routes under the soft time windows policy while minimizing total cost. The results demonstrate that the Hybrid Genetic Algorithm outperforms the initial solution in terms of total cost reduction. The initial routes are generated using the Nearest Insertion Heuristic and subsequently refined through mutation processes within the genetic algorithm framework.